Considerations for informed consent in the context of online, interactive, atlas creation - Browne, T.D.L. (Timothy Di Leo); Ljubicic, G. (Gita) (2019)
Creators of cybercartographic atlases must address the ethical considerations of their work, particularly the matter of informed consent. Digital technologies add a new element to the already complex issue of research ethics and consent, since information placed on the web is readily available to anyone with Internet access. In this chapter, a historical overview of ethics and informed consent in anthropological work is provided, as is a discussion of the particular problems posed by the digitization of local and traditional knowledge in widely accessible cybercartographic atlases. Feedback from Indigenous and non-Indigenous research organizations is presented with respect to these issues, and work conducted through Carleton University's Geomatics and Cartographic Research Centre is considered in the light of their feedback. Although definitive answers are not offered on some of the key challenges, methods to approach ethics and informed consent in the digital age are provided.